ANALISIS PENENTUAN INDUSTRI PRIORITAS KABUPATEN BLORA PROVINSI JAWA TENGAH - Medi Nopiana; Agus Maulana (Eqien - Jurnal Ekonomi dan Bisnis, 2016)
This research discusses identification of potentially viable industries to be developed as a priority industry in Regency of Blora. Methods of data analysis used is descriptive analysis, with four data collection methods, namely desk study, Focus Group Discussion (FGD), field observations and expert discussions. The data used are primary and secondary data. The results of analysis show that the industry elected as a priority industryin Regency of Blora arethose which are based on crafts and furniture (teak wood). This is due to the fact that the industry have high added-value products, unique in the region, have strong links to resources owned by the region, as well as having the opportunities to penetrate the international market. Keywords: Priority Industry, Competitiveness,Regency of Blora